A Geometry Deformation Model for Braided Continuum Manipulators - Sadati, S. M. Hadi; Naghibi, S. Elnaz; Shiva, Ali; Noh, Yohan; Gupta, Aditya; Walker, Ian D.; Althoefer, Kaspar; Nanayakkara, Thrishantha (Frontiers in Robotics and AI, 2017)
Continuum manipulators have gained significant attention in the robotic community due to their high dexterity, deformability and reachability. Modeling of such manipulators has been shown to be very complex and challenging. Despite many research attempts, a general and comprehensive modeling method is yet to be established. In this paper, for the first time, we introduce the bending effect in the model of a braided extensile pneumatic actuator with both stiff and bendable threads. Then, the effect of the manipulator cross section deformation on the constant curvature and variable curvature models is investigated using simple analytical results from a novel geometry deformation method and is compared to experimental results. We achieve 24% simulation accuracy using our constant curvature model for a braided continuum manipulator in presence of body load and 10% error using our variable curvature model in presence of extensive external loads. With proper model assumptions and taking to account the cross section deformation, an 8-20% increase in the simulation accuracy is achieved compared to a fixed cross section model. The presented models can be used for the exact modeling and design optimization of compound continuum manipulators by providing an analytical tool for the sensitivity analysis of the manipulator performance. Our main aim is the application in minimal invasive manipulation with limited workspaces and manipulators with regional tuneable stiffness in their cross section.